The complete chloroplast genome sequence of Begonia pedatifida - Huan Li; Tianlei Zhang; Jiale Liang; Xuan Tang; Zhuoyu Chenyang; Rong Zhu; Ying Chen; Qishan Kuang; Rongjie Huang; Hanbin Yin; Xingyu Zeng; Yongle Liu; et al. (Mitochondrial DNA. Part B. Resources)
Begonia pedatifida has persistently been utilized as a traditional folk herbal medicine. This study has sequenced the chloroplast genome of B. pedatifida to establish its genomic characteristics and to discern its phylogenetic relationships with other closely related species. The chloroplast genome structure of B. pedatifida reveals a circular molecule with a length of 169,606 bp, including a large single copy (LSC) region of 76,086 bp, a small single copy (SSC) region of 18,314 bp, and a pair of inverted repeats (IRS) region of 37,603 bp. The entire genome contains 138 genes, which consist of 88 protein-coding genes, 42 tRNA genes, and 8 rRNA genes. Phylogenetic analysis suggests that B. pedatifida is closely related to Begonia emeiensis, Begonia jinyunensis, and Begonia pulchrifolia, sharing a common ancestor and forming sister lineages. This research provides genetic information for further study on B. pedatifida.